Cynomolgus Monkeys With Spontaneous Type-2-Diabetes-Mellitus-Like Pathology Develop Alpha-Synuclein Alterations Reminiscent of Prodromal Parkinson’s Disease and Related Diseases - Sun, Yan; Guo, Chuang; Yuan, Lin; Li, Wen; Wang, Zhan-You; Yue, Feng; Li, Jia-Yi (Frontiers in Neuroscience, 2020)
Available evidence suggests that diabetes mellitus (DM) is a non-genetic risk factor for Parkinson’s disease (PD). PD and DM have shared similarities in pathogenetic mechanisms, including age, environmental factors, inflammatory reaction, and protein aggregation, etc. α-Synuclein is the primary protein component in the protein inclusions in PD, while islet amyloid polypeptide (IAPP) aggregates to form amyloid structures in  cells in type 2 diabetes mellitus (T2DM). Pancreatic and cerebral functions, pancrease and brain α-synuclein deposition as well as striatal alterations, were assessed in spontaneously developed T2DM monkeys and age-matched normal monkeys. We demonstrated increased accumulation, aggregation, and phosphorylation of α-synuclein, and IAPP in the pancreatic islets of spontaneously developed T2DM monkeys, compared to the age-matched normal subjects. Double immunofluorescence analyses showed complete overlap between α-synuclein and IAPP in the pancreatic islets. In addition, in T2DM monkeys’ brain, we observed concomitantly increased accumulation and phosphorylation of α-synuclein in the cortex, striatum and dopaminergic neurons in the substantia nigra, which interestingly showed high correlation with levels of fasting plasma glucose (FPG), triglyceride (TG) and high density lipoprotein (HDL). Our data indicates the close association between IAPP and α-synuclein and the potential link between T2DM and PD, which implies that T2DM may facilitate PD disease onset and progress by interfering with the pathological protein aggregation both in the pancreatic islets and the brain.